Pengaruh Gaya Kepemimpinan, Motivasi Kerja, dan Partisipasi terhadap Prestasi Kerja Karyawan pada Seis Cafe & Public Space di Kota Medan: Penelitian - Togu Bonardo; Nicholas Marpaung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Seis Cafe & Public Space in Medan City is a business that prioritizes innovation in both design and service. Work performance is an essential aspect in maintaining service quality. This performance is influenced by various factors, including leadership style, work motivation, and employee participation. The purpose of this research is to analyze the influence of leadership style, work motivation, and participation on work performance at Seis Cafe & Public Space in Medan City. This study employs a quantitative method with an associative approach. The research sample was taken using a total sampling technique consisting of 30 respondents. Primary data were obtained through questionnaires, while secondary data were collected through literature studies. Data analysis techniques included classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results show that leadership style, work motivation, and participation have a positive and significant influence, both partially and simultaneously, on work performance. The coefficient of determination indicates a very strong relationship with an R value of 0.932, while the adjusted R square shows that the independent variables contribute 85.4% to employee performance, with the remaining 14.6% influenced by other factors outside this study.